Adoption of AI in entrepreneurship education: University teachers’ perceptions - Belguith, Marwa (International Journal of Advances in Educational Research, 2025)
This article investigates university teachers' perceptions of innovative pedagogical approaches in entrepreneurship education, particularly those integrating digital technologies with a focus on artificial intelligence (AI). It highlights AI’s potential to personalize learning paths, support adaptive feedback, and facilitate more nuanced and contextualized assessments of students' entrepreneurial competencies. Drawing on a qualitative study involving 147 university instructors through semi-structured interviews, the research explores their current teaching practices, attitudes toward AI integration, and concrete suggestions for its effective and ethical use. The results reveal a range of influencing factors, including digital literacy, institutional support, and pedagogical orientations, which shape the willingness and readiness of instructors to adopt AI-driven tools. The study also discusses barriers to adoption such as limited resources and concerns over the human dimension of teaching while emphasizing opportunities for enhancing engagement, autonomy, and innovation in entrepreneurship education through AI.